Effect of Chemically Engineered Au/Ag Nanorods on the Optical and Mechanical Properties of Keratin Based Films - Gambucci, Marta; Aluigi, Annalisa; Seri, Mirko; Sotgiu, Giovanna; Zampini, Giulia; Donnadio, Anna; Torreggiani, Armida; Zamboni, Roberto; Latterini, Loredana; Posati, Tamara (Frontiers in Chemistry, 2020)
In this work we report the preparation and characterization of free-standing keratin-based films containing Au/Ag nanorods. The effect of nanorods surface chemistry on the optical and mechanical properties of keratin composite films is fully investigated. Colloid nanorods confer to the keratin films interesting color effects due to plasmonic absorptions of the metal nanostructures. The presence of metal NRs induces also substantial change in the protein fluorescence emission. In particular, the relative contribution of the ordered-protein aggregates emission is enhanced by the presence of cysteine and thus strictly related to the surface chemistry of nanorods. The presence of more packed supramolecular structures in the films containing metal nanorods (in particular cysteine modified ones) is confirmed by ATR measurements. In addition, the films containing nanorods show a higher Young’s modulus compared to keratin alone and again the effect is more pronounced for cysteine modified nanorods. Collectively, the reported results indicate the optical and mechanical properties of keratin composites films are related to a common property and can be tuned simultaneously, paving the way to the optimization and improvement of their performances and enhancing the exploitation of keratin composites in highly technological optoelectronic applications.